Investigation of Human Resources Applications from Sustainability Perspective: An Empirical Study - Ozgul, Burcu; Bozkurt, Serdar; Gurol, Yonca (ISTANBUL UNIV, SCH BUSINESS, 2020)
This study conducted between November 2017 and October 2018 investigates companies included in the stock market sustainability index (BIST) in Istanbul. The focus of the research was on whether or not their sustainability works/ projects materialized, which shareholders were involved in this process and whether sustainability was integrated into their company activities. In addition, the issue of the relationship between sustainability studies and human resources applications and the question of whether or not human resources took a strategical role were investigated. 18 of the 44 companies included in the BIST Sustainability Index (41%) participated in the study. The result of the study shows that companies integrated sustainability into their corporate policies. Furthermore, the companies internalized sustainability with the aims of increasing corporate dignity and brand value, contributing to economic and social recovery, improving relations with shareholders and gaining trust from public opinion.
Keywords: Corporate sustainability; BIST sustainability index; Strategic human resources management; Sustainable human resources management; CORPORATE SOCIAL-RESPONSIBILITY; WORK-LIFE BALANCE; ORGANIZATIONAL JUSTICE; MANAGEMENT; SYSTEMS; PERFORMANCE; EMPLOYEES; IMPACT; PERCEPTION; BEHAVIORS; Business & Economics